Analysis Of The Value Of Regional Revenue And Expenditure Budget (APBD) In The Bkad Of North Sumatera Utara - Aliya, Farah; Ramadhan, Puja Rizqy; Nasution, Anggi Pratama (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This research aims to evaluate the financial performance of the Regional Financial and Asset Management Agency (BKAD) of North Sumatra from 2020 to 2024 using the Value for Money framework. The researcher applied a descriptive quantitative methodology, relying on primary and secondary data sourced from literature studies and Budget Realization Report (LRA) documentation. The study's findings indicate variations in performance across three main pillars. The effectiveness level is classified as highly satisfactory, remaining stable in the 'Effective' and 'Very Effective' categories, even reaching 276% in 2022. However, the efficiency ratio shows sharp instability, with most periods falling under the 'Inefficient' level, except for an anomaly in 2022 of 8928% triggered by low expenditure absorption. On the other hand, the economic dimension continues to improve, moving from a level of 102% ('Uneconomical') in 2020 to a range of 77-78% ('Economical') in the 2023-2024 period. In general, the BKAD of North Sumatra Province has been able to maximize revenue and control expenditure, although the synchronization of expenditure efficiency relative to income still needs to be improved.